How does whole body balance control interact with stroke performance during the tennis serve? - Jamkrajang, P.; Robinson, M.; Limroongreungrat, W.; Vanrenterghem, J. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to investigate whether there is an interaction between mechanisms used to control whole body balance and racket performance. Fourteen experienced tennis players (nine males and five females; age, 21.5±3.9 yr; height, 1.7± 0.1 m; body mass 65.8± 8.1 kg) completed 10 successful tennis serves. Twelve optoelectronic cameras were used to collect kinematic data at 200 Hz (BTS bioengineering, Milan, Italy). Linear regression using 1D Statistical Parametric Mapping was used to identify interactions between the extrapolated centre of mass (XCoM) displacement in the anteroposterior direction and the changes in arms/trunk segment angular momentum, and peak anterior-posterior racket velocity. Overall, no meaningful relationships were found, except for a small time interval during the forward swing phase in which a greater increase in trunk angular momentum was associated with increased maximum racket velocity.